SALIVA ACIDITY LEVEL TOWARD APPLICATION CASEIN PHOSPHOPEPTIDE - AMORPHOUS CALCIUM PHOSPHATE FOR CHILDREN AGED 8-9 YEARS - Apriani, Anie; Mandalas, Henry Yonatan; Khoe, William (Faculty of Dentistry, Universitas Islam Sultan Agung, 2021)
ABSTRACTBackground: Dental caries is a disease of dental hard tissue that is often found in children. The etiology of dental caries is very diverse and multifactorial, one of which is the decreased acidity of saliva. There are many efforts and ways to reduce the incidence of dental caries, one of which is the application of topical flour to the teeth. Casein phosphopeptide–amorphous calcium phosphate (CPP-ACP) as a type of topical flour used has been shown to reduce demineralization and increase tooth remineralization. This study aimed to determine the acidity level of saliva before and after application of CPP-ACP in children aged 8-9 years. Methods: Measurement of salivary acidity was measured using a digital pH meter in the study sample of 42 children consisting of 23 boys and 19 girls. Subjects were applied CPP-ACP for 1 month with the routine application once a week, then re-examined the salivary acidity level after 1 month. Result : The average result of salivary acidity before CPP-ACP application was 6.928 and after CPP-ACP application was 7.0611. The T-test resulted in a very significant difference in the level of salivary acidity before and after the application of CPP-ACP. Conclusion : is that Tthere are differences in the level of salivary acidity in children aged 8-9 years before and after topical application of CPP-ACP flour.